Loss of Saltation and Presynaptic Action Potential Failure in Demyelinated Axons - Hamada, Mustafa S.; Popovic, Marko A.; Kole, Maarten H. P. (Frontiers in Cellular Neuroscience, 2017)
In cortical pyramidal neurons the presynaptic terminals controlling transmitter release are located along unmyelinated axon collaterals, far from the original action potential (AP) initiation site, the axon initial segment (AIS). Once initiated, APs will need to reliably propagate over long distances and regions of geometrical inhomogeneity like branch points (BPs) to rapidly depolarize the presynaptic terminals and confer temporally precise synaptic transmission. While axon pathologies such as demyelinating diseases are well established to impede the fidelity of AP propagation along internodes, to which extent myelin loss affects propagation along BPs and axon collaterals is not well understood. Here, using the cuprizone demyelination model, we performed optical voltage-sensitive dye (VSD) imaging from control and demyelinated layer 5 pyramidal neuron axons. In the main axon, we find that myelin loss switches the modality of AP propagation from rapid saltation towards a slow continuous wave. The duration of single AP waveforms at BPs or nodes was, however, only slightly briefer. In contrast, by using two-photon microscopy-guided loose-seal patch recordings from axon collaterals we revealed a presynaptic AP broadening in combination with a reduced velocity and frequency-dependent failure. Finally, internodal myelin loss was also associated with de novo sprouting of axon collaterals starting from the primary (demyelinated) axon. Thus, the loss of oligodendrocytes and myelin sheaths bears functional consequences beyond the main axon, impeding the temporal fidelity of presynaptic APs and affecting the functional and structural organization of synaptic connectivity within the neocortex.